Rodzice wobec dorosłości swoich dzieci z niepełnosprawnością intelektualną - Cytowska, Beata (Karkonoska Państwowa Szkoła Wyższa, 2011)
The Author has chosen the intellectual disability to be the topic of her divagations. Therefore she enumerates certain factors which make the process of growing up more difficult or sometimes even impossible for people with intellectual disability. The article involves the analysis of several interviews with parents of adult children with intellectual disability. The main subject of those conversations was the perception of their children's adulthood.
Keywords: adulthood; parents; intellectual disability; interviewing; family